Spatial Variability of Fruit and Seedling Growth of Mindi (Melia azedarach L.) in Community Forest, West Java, Indonesia - Irmayanti, Laswi; Siregar, Iskandar Zulkarnaen; Pamoengkas, Prijanto (Journal of Tropical Life Science, 2015)
Mindi (Melia azedarach L.) is mostly found in community forests of West Java. One of the important factors affecting productivity of community forests is the use of quality seed. Due to scarcity of seed sources, however, seed quality is not easily available. Currently, community forests serve also as ad hoc seed sources that are usually without appropriate quality assessment. This research was aimed to determine baseline information on spatial variability of mindi fruits collected from five seed sources, and seedling growths treated in seven different growing media consisting mixtures of soil, rice husk, sand and cattle manure. Five mindi populations were selected in the following villages: Nagrak (Bogor), Babakan Rema (Kuningan), Padasari (Sumedang), Sukakarya (Bogor) and Gambung (Bandung). The results showed that variability of seed dimension (CV=4.82-14.37%) and seedling growth (11.79-21.77%) were moderate. The mindi fruits from Nagrak were found to be the biggest in terms of size (1.22 ± 0.17 cm), weight (0.40 ± 0.04 g), and seed set (85.47 ± 15.09%). In addition, the seedling growth from Nagrak was also better than those of other villages showing its potential for future seed sources. Growing media containing cattle manure were observed consistently to be the best for seedling growth. The findings are useful in supporting scientifically the selection of seed sources from community forests.